Does Sharia Financial Literacy of MSMEs Influencing in Sharia Banking Financing: Investigating the Creative Economy - Habriyanto; Budi Trianto; Nik Hadiyan Nik Azman; Busiradi; Evan Hamzah Muchtar; Elida Elvi Barus (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
This study aims to determine what factors influence MSMEs in the creative economy sector in deciding on Islamic Banking financing in Indonesia. We investigated the role of Islamic financial awareness, Islamic financial knowledge, and Islamic financial skills. We also examine whether the decision to use Islamic Banking financing impacts business performance. By using a path analysis approach, the results of this study show that Islamic financial awareness and financial skills positively impact the decision to finance in Islamic banking. Meanwhile, the decision to finance in Islamic banking has a positive effect on business performance, but insignificant. Other results show that Islamic financial skills positively and significantly impact MSME business performance. The results of this study imply that business actors in the creative economy sector must be given an understanding of Islamic financial skills and Islamic financial awareness. On the other hand, Islamic banking must expand financing in the creative economy sector through a more competitive financing scheme so that MSMEs can easily access it. Expanding access to Islamic financing for MSMEs is expected to accelerate the inclusion of Islamic finance in Indonesia. This study is a preliminary investigation in Indonesia of Islamic Banking Financing for the creative economy.